2013
DOI: 10.1155/2013/723160
|View full text |Cite
|
Sign up to set email alerts
|

Acute Gastric Dilatation: A Transient Cause of Hepatic Portal Venous Gas—Case Report and Review of the Literature

Abstract: Gastric pneumatosis (GP) and hepatic portal venous gas (HPVG) have typically been thought of as an ominous radiological sign associated with a grave prognosis, and the observation of HPVG on plain abdominal radiography, ultrasonography, or computed tomography is viewed as a significant finding. It is often associated with severe or potentially lethal conditions warranting urgent diagnosis and possible surgical intervention. Early studies of HPVG based on plain abdominal radiography found an associated mortalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 26 publications
(34 reference statements)
0
15
0
Order By: Relevance
“…Although the presence of gas in the portal venous system was generally considered to be a serious intra-abdominal event, many benign cases have been put forward with the development of imaging modalities. Our search for reported cases of HPVG during the most recent 5 years (table 2 ) [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ] revealed that 20 of the 31 patients were treated by a nonsurgical approach, and 22 (71%) of the 31 patients recovered, suggesting that HPVG is not always a fatal sign in those patients. In addition, invasive therapy, including chemotherapy, endoscopic retrograde cholangiopancreatography, and CT-guided aspiration biopsy, was performed in 14 (45.2%) of the 31 patients before onset of HPVG.…”
Section: Discussionmentioning
confidence: 99%
“…Although the presence of gas in the portal venous system was generally considered to be a serious intra-abdominal event, many benign cases have been put forward with the development of imaging modalities. Our search for reported cases of HPVG during the most recent 5 years (table 2 ) [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ] revealed that 20 of the 31 patients were treated by a nonsurgical approach, and 22 (71%) of the 31 patients recovered, suggesting that HPVG is not always a fatal sign in those patients. In addition, invasive therapy, including chemotherapy, endoscopic retrograde cholangiopancreatography, and CT-guided aspiration biopsy, was performed in 14 (45.2%) of the 31 patients before onset of HPVG.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic portal venous gas (HPVG) was described more than 55 years ago and is commonly associated with intramural bowel gas called pneumatosis intestinalis [1]. The frequency of detection of HPVG and pneumatosis intestinalis appears to be increasing.…”
Section: Discussionmentioning
confidence: 99%
“…[2,4]. The overall mortality rate can be as high as 75-90%, depending on the underlying etiology [1,5]. In last decades, mortality rate seems to be lower, and is considered to be the result of early diagnosis as well as its association with unimportant causes, in which conservative management is more beneficial [6].…”
Section: Discussionmentioning
confidence: 99%
“…HPVG is generally considered an alarming radiological sign as it is associated with high mortality in all age groups [1,2]. The most common recognized life threatening conditions leading to portal venous gas include ischemic necrotic bowel, necrotizing enterocolitis, intra-abdominal abscess, inflammatory bowel disease, acute hemorrhagic pancreatitis, gastric ulcer and diabetic ketoacidosis [3][4][5].…”
Section: Introductionmentioning
confidence: 99%